If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -8 + -2y + 3 = 0 Reorder the terms: -8 + 3 + 6y + -2y = 0 Combine like terms: -8 + 3 = -5 -5 + 6y + -2y = 0 Combine like terms: 6y + -2y = 4y -5 + 4y = 0 Solving -5 + 4y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 4y = 0 + 5 4y = 0 + 5 Combine like terms: 0 + 5 = 5 4y = 5 Divide each side by '4'. y = 1.25 Simplifying y = 1.25
| 6n+1=.5 | | (x+y+z)(x+y)-(x-y-z)(x-y)= | | 4+4q=9+3q | | 7*4p-5*3r+3*3q-5*5r+4*5q-10q= | | 3x/4-12=3 | | 2w+1+w=18 | | 0.36(24)+0.04=0.12(6+x) | | 11*11/12-3 | | 8x+4=-2(6x-1) | | y-5=2/4(x-2) | | 7x+5(2+x)=-2 | | (1/3)8 | | 3-4x=2x+25 | | 6x+3=34x+7 | | 23-[3+9y-3(y+3)]=-3(4y-6)-[8(y-1)-10y+13] | | 3(2x+6)+12=-15 | | 5(1-3m)=30-(4m+7) | | 3x-4.9=0 | | x^2-3ax-10a^2=0 | | 7y+6=2y-9 | | 12(3x+4)-5(2x-5)=6x-67 | | 13r+16=5t | | -5-10b=15-11b | | (0.2x+3)(0.2x-3)=0 | | 4[x+2(5-x)]=3x+1 | | 15+11h=10h | | 12y-6+2y+8=12solve | | 5x-3x=7 | | -15+3j=13+5j | | x^2-0.4x+0.0425=0 | | 3+6x=x+16 | | A(x)=4x^2+20x |